Investor experience and innovation performance: The mediating role of external cooperation - Boh, Wai Fong; Huang, Cheng‐Jen; Wu, Anne (Strategic Management Journal, 2020)
Abstract Research Summary We add to the literature examining the ownership‐innovation relationship by examining two major investor types: corporate investors and family investors. We use organizational environmental scanning as a new perspective to understand how these investors' capabilities influence firms' external cooperation and innovation performance. We found that corporate investors with broad investment experience strengthen a firm's environmental scanning, enhancing innovation performance by increasing the number of external cooperation activities the firm engages in. Conversely, family investors' broad investment experience tend to be negatively associated with the number of external cooperation and with firm innovation. Our results show that investors influence firm innovation not simply through a monitoring role but also by affecting firms' abilities to innovate, once we factor in the types of investors and their capabilities. Managerial Summary We investigate how two different types of investors, corporate and family, influence the innovation performance of publicly‐traded high‐tech firms in Taiwan. We found that the presence of major corporate investors with broad investment experience enhances firms' innovation performance by increasing external cooperation activities firms engage in. Corporate investors appear to enhance organizations' environmental scanning abilities and, in turn, their innovation performance. Conversely, family investors' broad investment experience is negatively associated with firm innovation because such firms engage in fewer external cooperation activities. A focus on control and social cohesion in family firms appears to decrease the emphasis on external knowledge acquisition when family investors have broad investment experience. In summary, our results show that investors' breadth of investment experience influences firms' ability to innovate.